The NAD+ Responsive Transcription Factor ERM-BP Functions Downstream of Cellular Aggregation and Is an Early Regulator of Development and Heat Shock Response in Entamoeba - Dipak Manna; Daniela Lozano-Amado; Gretchen Ehrenkaufer; Upinder Singh; Upinder Singh (Frontiers in Cellular and Infection Microbiology, 2020)
Entamoeba histolytica is a protozoan parasite and a major cause of dysentery and diarrheal disease in developing countries. Disease transmission from one host to another occurs via cysts which can survive in environmental extremes and are transmitted through contaminated food and water. Recent studies in our lab identified a novel transcription factor, Encystation Regulatory Motif- Binding Protein (ERM-BP), which is responsive to NAD+ and has an important role in encystation. The key residues important for ERM-BP function were demonstrated in vitro using recombinant protein. In this study we demonstrate the in vivo functional consequences of mutations in key domains and their impact on Entamoeba encystation. Our results show that mutations in the DNA binding domain (ERM-BP-DBM) and in the nicotinamidase domain (ERM-BP-C198A) lead to protein mis-localization in both trophozoites and cysts and significantly reduce encystation efficiency. Additionally, we showed that silencing of ERM-BP significantly decreased the size and number of multi-nucleated giant cells (MGC) that form during encystation, indicating that ERM-BP functions upstream of the cellular aggregation that precedes stage conversion. Dissection of epistatic interactions between ERM-BP and a second encystation-related transcription factor, NF-Y revealed that ERM-BP is upstream of NF-Y in controlling the developmental cascade and appears to be one of the earliest regulators of development identified to date in Entamoeba. We also demonstrated that ERM-BP is upregulated during heat stress in Entamoeba, another condition which increases intracellular NAD+ levels and that overexpression of ERM-BP makes E. histolytica and E. invadens parasites more resistant to heat stress. Overexpression of ERM-BP in E. histolytica also induced the formation of cyst-like quadrinucleated cells and formation of MGCs. Overall, our work has identified an important role of ERM-BP in Entamoeba stress response and links an NAD+-responsive transcription factor to both development and heat shock response. Characterization of stress and developmental cascades are important avenues to investigate for Entamoeba, an important human parasitic pathogen.